Callus Induction and Plant Regeneration from Leaf Segments of Unique Tropical Woody Plant Parasponia andersonii Planch (Plant Tissue Culture and Biotechnology, 2018)
The purpose of the present study was to develop effective methods for callus induction, shoot regeneration, and rooting for Parasponia andersonii. Leaf explants of P. andersonii were placed on Lloyd and McCown’s (WPM) medium supplemented with various concentrations of TDZ and NAA for callus induction. Callus induction was observed on media containing 0.1 - 0.2 mg/l TDZ with 0.05 mg/l NAA. Maximum shoot regeneration was observed when the calluses were cultured on MS supplemented with TDZ and IBA. Shoots cultured on WPM medium supplemented with 0.5 mg/l IBA had the maximum rooting percentage (100) in 3 weeks. Rooted plants were transplanted to a potting mixture containing vermiculite (50%) and peat (50%) (v/v). After 2 months, more than 20% of plants survived and were transferred to the greenhouse. Thus, a new effective method has been developed for P. andersonii micropropagation that can be used in studies of plant-Rhizobium symbiosis and for the generation of transgenic Parasponia plants.Plant Tissue Cult. & Biotech. 28(1): 45-55, 2018 (June)